What you should know about inflation - Hazlitt, Henry; United States (Princeton, N.J.: Van Nostrand, 1960)
The book consists of 44 very brief chapters totaling 152 pages; the book constantly emphasizes the virtues of the free enterprise system. In brief, it highlights what the reader should know about inflation includes: (1) Inflation penalizes thrift, encourages gambling, and in many other ways undermines the free enterprise system. (2) Increases in the supply of money are essentially the only cause of inflation. (3) Increases in the money supply occur solely as a result of government action. (4) Willingness to restore the gold (coin) standard is probably a necessary and sufficient condition for halting inflation- a long section of the book examines this topic and how to achieve the return without deflation. (5) There is not or should not be any real conflict between price stability and other objectives.
usc 14/05/2018
Loans
Keywords: Inflation (Finance)